The status of Turkish nomadic people (yürük) in the Ottoman Empire territory in the 15th and 16th centuries - Mikołajczak, Marcin (Balcanica Posnaniensia. Acta et studia, 2007)
The aim of this article is to analyse the legal and social position of Turkish nomads (yürüków) in the Ottoman Empire in the light of normative sources, especially kanunnames, i.e. codes issued by sultans since the time of Mehmed II the Conqueror. The source material consists of kanunname texts, fermans and other sultanic regulations that defined the obligations and privileges of nomads towards the state. The method used was to analyse legal sources and compare them with demographic and economic data from, among others, tax registers and calculations by contemporary researchers. The findings indicate that the yürük initially played an important role in the Ottoman military system, providing specialised cavalry and militia units. However, their military significance declined, while administrative control and tax burdens increased. The nomads were subject to supervision by both central and local authorities. This led to the weakening of tribal structures and the gradual decline of the yürük. While maintaining the appearance of their former independence, they were largely integrated into the Ottoman administrative and fiscal system.